2020
DOI: 10.1159/000510684
|View full text |Cite
|
Sign up to set email alerts
|

Nephrometry Scores: Can Preoperative Assessment of Sectional Imaging Really Mirror Intraoperative Renal Tumor Anatomy?

Abstract: <b><i>Introduction:</i></b> To compare RENAL, preoperative aspects and dimensions used for an anatomical (PADUA) classification, and Mayo Adhesive Probability (MAP) scores with the respective intraoperative findings and surgeon’s assessment in predicting surgical outcome of patients undergoing partial nephrectomy. <b><i>Methods:</i></b> Data of 150 eligible patients treated at the University Medical Center Mannheim between 2016 and 2018 were analyzed. Tumors were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…None of the nephrometry scores were superior predictor compared to other nephrometry scores. Egen et al, in a single center study including 150 patients, also support our finding that RENAL, PADUA, and Mayo Adhesive Probability (MAP) scores were independent predictors of the Trifecta ( 24 ). Crockett et al reported the outcomes of 322 RAPNs, and evaluated RENAL, PADUA, and Simplified PADUA REnal classification (SPARE) scores.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…None of the nephrometry scores were superior predictor compared to other nephrometry scores. Egen et al, in a single center study including 150 patients, also support our finding that RENAL, PADUA, and Mayo Adhesive Probability (MAP) scores were independent predictors of the Trifecta ( 24 ). Crockett et al reported the outcomes of 322 RAPNs, and evaluated RENAL, PADUA, and Simplified PADUA REnal classification (SPARE) scores.…”
Section: Discussionsupporting
confidence: 85%
“…The external validation studies demonstrated that nephrometry scores associated with perioperative and renal functional outcomes ( 14 16 , 23 ). However, there are only four studies on comparative analysis of nephrometry scores to predict the Trifecta success ( 8 , 20 , 23 , 24 ). In our study, RENAL, PADUA, and C-index scores were all helpful to independently predict the strict Trifecta outcomes.…”
Section: Discussionmentioning
confidence: 99%